Unraveling the Steric Link to Copper Precursor Decomposition: A Multi‐Faceted Study for the Printing of Flexible Electronics. Issue 4 (19th February 2023) - Mrig, Shreya; Bhide, Malavika A.; Zhou, Ye; Stanton, Nils; Wang, Jingyan; Douglas, Samuel P.; Tinker, Henry R.; Mears, Kristian L.; Bakewell, Clare M.; Knapp, Caroline E.
Abstract: The field of printed electronics strives for lower processing temperatures to move toward flexible substrates that have vast potential: from wearable medical devices to animal tagging. Typically, ink formulations are optimized using mass screening and elimination of failures; as such, there are no comprehensive studies on the fundamental chemistry at play. Herein, findings which describe the steric link to decomposition profile: combining density functional theory, crystallography, thermal decomposition, mass spectrometry, and inkjet printing, are reported. Through the reaction of copper(II) formate with excess alkanolamines of varying steric bulk, tris‐co‐ordinated copper precursor ions: "[CuL3 ], " each with a formate counter‐ion (1–3) are isolated and their thermal decomposition mass spectrometry profiles are collected to assess their suitability for use in inks (I 1–3 ). Spin coating and inkjet printing of I 1, 2 provides an easily up‐scalable method toward the deposition of highly conductive copper device interconnects ( ρ = 4.7–5.3 × 10 −7 Ω m; ≈30% bulk) onto paper and polyimide substrates and forms functioning circuits that can power light‐emitting diodes. The connection among ligand bulk, coordination number, and improved decomposition profile supports fundamental understanding which will direct future design. Abstract : Single crystal X‐ray diffraction investigation alongside density functional theory calculations establishes a link between the geometry of copper precursors and their decomposition to copper metal. Precursor synthesis and their decomposition profiles are reported. Inkjet printing yields conductive ( ρ = 4.7–5.3 × 10 −7 Ω m; ≈30% bulk) copper features onto paper and polyimide substrates at 125 °C and 150 °C.